دور الإدارة في تنظيم الانتخابات في الجزائر -خلال الفترة 2018/2022- - فراحتية عبد القادر (جامعة المسيلة, 2022)
يعد الانتخاب الوسيلة الأساسية لإسناد السلطة، وتكريس إرادة الشعب في صنع القرار السياسي، لأن السيادة ملك للشعب يمارسها عن طريق ممثليه، ومنه من الطبيعي القول بأن سلامة الديمقراطية ونجاحها يتوقفان مع سلامة العملية الانتخابية ،والسلطة الوطنية المستقلة للانتخابات اعتبرت مطلبا أساسيا للحراك الشعبي في الجزائر، الذي جعل النزاهة العملية الانتخابية وسلامة أصوات الناخبين من التلاعب والتزوير أولوية قصوى ،وتمت الاستجابة لهذا المطلب من خلال إصدار القانون العضوي 19-07 المنظم لها، والذي تضمن صلاحيات غير مسبوقة للسلطة المستقلة في مجال تنظيم الانتخابات. الكلمات المفتاحية: الإدارة العامة، مبدأ الحياد، الانتخابات، اللجنة المستقلة للانتخابات Abstract Election is the primary means of assigning power, and consolidating the will of the people in political decision-making, because sovereignty belongs to the people who exercise it through their representatives, and it is natural to say that the integrity and success of democracy depends on the integrity of the electoral process, and the independent national authority for elections was considered a basic requirement for the popular movement in Algeria. Which made the integrity of the electoral process and the safety of voters’ votes from fraud and manipulation a top priority, and this demand was responded to by issuing the Organic Law 19-07 regulating it, which included unprecedented powers for the independent authority in the field of organizing elections. Keywords: public administration, the principle of impartiality, elections, the Independent Electoral Commission
Keywords: الإدارة العامة، مبدأ الحياد، الانتخابات، اللجنة المستقلة للانتخابات